COVID-19 and Clostridioides difficile Coinfection Analysis in the Intensive Care Unit - Mircea Stoian; Adina Andone; Alina Boeriu; Sergio Rareș Bândilă; Daniela Dobru; Sergiu Ștefan Laszlo; Dragoș Corău; Emil Marian Arbănași; Eliza Russu; Adina Stoian (Antibiotics, 2024)
Since the emergence of SARS-CoV-2 in late 2019, the global mortality attributable to COVID-19 has reached 6,972,152 deaths according to the World Health Organization (WHO). The association between coinfection with Clostridioides difficile (CDI) and SARS-CoV-2 has limited data in the literature. This retrospective study, conducted at Mureș County Clinical Hospital in Romania, involved 3002 ICU patients. Following stringent inclusion and exclusion criteria, 63 patients were enrolled, with a division into two subgroups—SARS-CoV-2 + CDI patients and CDI patients. Throughout their hospitalization, the patients were closely monitored. Analysis revealed no significant correlation between comorbidities and invasive mechanical ventilation (IMV) or non-invasive mechanical ventilation (NIMV). However, statistically significant associations were noted between renal and hepatic comorbidties (p = 0.009), death and CDI-SARS-CoV-2 coinfection (p = 0.09), flourochinolone treatment and CDI-SARS-CoV-2 infection (p = 0.03), and an association between diabetes mellitus and SARS-CoV-2-CDI infection (p = 0.04), as well as the need for invasive mechanical ventilation (p = 0.04). The patients with CDI treatment were significantly younger and received immuno-modulator or corticotherapy treatment, which was a risk factor for opportunistic agents. Antibiotic and PPI (proton pump inhibitor) treatment were significant risk factors for CDI coinfection, as well as for death, with PPI treatment in combination with antibiotic treatment being a more significant risk factor.